Соціологічний аспект сутності феномену успіху - Ярема, Анастасія (Видавництво Національного університету "Львівська політехніка", 2009)
Specificity of sociological approach to investigation of the notion «success» is outlined. The concept of «success» is examined at personal and social level of analysis, what gives an opportunity to differentiate between the conceptions of «life success» and «social success». Social success is concerned as socially significant and recognized result of person’s social actions, unlike the term «life success», which fixes persons subjective estimation of its own social practices. The author offers own definition, considering social success as socially meaningful result of agent’s social practices in the significant field of activity, using legitimate methods.
Keywords: success; social practices; life success; social success